MENGUKUR DAMPAK PELATIHAN TERHADAP IMPLEMENTASI BUDAYA KERJA PRODUKTIF DALAM RANGKA PENINGKATAN PRODUKTIVITAS MENGGUNAKAN SMARTPLS - Nuraeni, Yeni; Nasution, Faizal Amir; Maulana, Zusfarlian (PATTIMURA UNIVERSITY, 2021)
The competitiveness of Indonesian workers is still lagging behind several countries in the world. For this reason, the Indonesian government needs to increase labor productivity which is a component of competitiveness. One of the efforts is to organize training related to work productivity. This study aims to evaluate and analyze the impact of productivity training programs organized by the government on the implementation of productive work culture in Indonesia. This study uses quantitative data analysis in the form of path analysis using SmartPLS software. The results show that productive work culture can encourage work productivity, job training can encourage Kaizen culture, and a productive work culture directly, but job training does not directly encourage work productivity. Kaizen culture has a positive and significant relationship to work productivity indirectly, but through the 5S culture first. The productivity improvement training program and consulting guidance by the government need to pay attention to the dominant work culture applied by companies to achieve high work productivity.